Human Skin Bank In Malaysia: Addressing Clinical Demands Through Islamic Shariah Perspectives - Muhamad Rafiqi Hehsan (Universiti Sains Islam Malaysia, 2025)
Journal of Fatwa Management and Research, Volume 30 Issue 3 Page (14-38)